Comparative analysis of frequently used e-learning platforms - Jain, Shaily; Prabha, Chander; Nandan, Durgesh; Bhosale, Snehal (Frontiers in Education, 2024)
An online e-learning platform referring Learning Management System (LMS) provides an interface between trainer, students, and administrator towards a common objective of learning. In the market, diverse LMS with enormous functionalities are available to help us in e-learning. In this paper, we picked some popular LMSs majorly used by most schools and institutions for their teaching-learning process. We have compared these LMS in a discussion based on their technical specifications, technical features, administrative features, general features, and also course management-related features. This comparative analysis will help users to decide which LMS suits best according to their requirements. We also try to find the limitations of these learning management systems so that users and organizations can check out which one is best suited for them.